Satua I Srabena I Srabeni: Kajian Sastra Antropologis - Dewi Juliana, Ni Komang; Suryati, Ni Made; Puspawati, Luh Putu (Humanis, 2018)
The study of Satua I Srabeni I Srabena discusses the analysis of literary structure and anthropology. This analysis aims to reveal the building structures and values ??of Balinese culture embodied in Satua I Srabena I Srabeni.This research uses structural theory, text theory, and theory of Literary Anthropology. Methods and techniques used in this study are divided into three stages, namely 1) methods and techniques of data provision using simak method assisted by transcription techniques, record techniques, and translation techniques, 2) methods and techniques of data analysis using qualitative methods and descriptive analytic techniques , 3) methods and techniques of presenting the results of data analysis using informal methods and deductive and inductive techniques. The result of this research is narrative strutur which includes eight incident, using straight groove and groove is divided into five stages, namely: situation stage, generating circumstances stage, rising action stage, climax stage, and denouement stage. Characters and characterizations are divided into three namely: the main character is I Srabena I Srabeni, secondary figures namely Father, and complementary figures (complementary) ie a couple husband, wife of Anak Agung, Anak Agung, wife Jin, Jin. Background is divided into three, namely: the background of the place that is on the road, jumah, gerobag, park, alase, diwangan, punyan bingin, ampike, and pasisi, background time is peteng, ibi sanja, and weak and background atmosphere angry atmosphere, , longing, anxiety, fear, and threatening atmosphere. The theme of women, about women in good behavior should be done by women and contained a mandate on how to respect women and behave well in life. The results of the literary anthropological research in this satua reveal the values ??of the culture contained, namely the value of vital, social values, ethical values, human values, sacred values, and the value of rwa Bhinneda contained in the four elements of culture in the story.